2015
DOI: 10.1159/000438594
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes Improve the Microenvironment of Infarcted Myocardium Contributing to Angiogenesis and Anti-Inflammation

Abstract: Background/Aims: Bone marrow mesenchymal stem cells (MSCs) widely applied for treating myocardial infarction face survival challenges in the inflammatory and ischemia microenvironment of acute myocardial infarction. The study hypothesized that MSC-derived exosomes play a significant role in improving microenvironment after acute myocardial infarction and aimed to investigate the paracrine effects of exosomes on angiogenesis and anti-inflammatory activity. Methods: MSCs were cultured in DMEM/F12 supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
291
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 406 publications
(299 citation statements)
references
References 27 publications
5
291
0
3
Order By: Relevance
“…Feng et al31 demonstrated that exosomes released from ischemic preconditioned MSCs contained an increased amount of miR‐22, which could exert a silence effect on methyl CpG binding protein 2 to ameliorate apoptosis in mice with AMI. Our group also proved that MSC‐derived exosomes could inhibit inflammation, augment vasculogenesis, and restore cardiac function in MI by activating and modifying the microRNA profiles of cardiac stem cells 32, 33. Despite these therapeutic effects of MSCs‐exosomes, targeting intended tissues or cells while avoiding nonintended delivery still remains challenging.…”
Section: Discussionmentioning
confidence: 89%
“…Feng et al31 demonstrated that exosomes released from ischemic preconditioned MSCs contained an increased amount of miR‐22, which could exert a silence effect on methyl CpG binding protein 2 to ameliorate apoptosis in mice with AMI. Our group also proved that MSC‐derived exosomes could inhibit inflammation, augment vasculogenesis, and restore cardiac function in MI by activating and modifying the microRNA profiles of cardiac stem cells 32, 33. Despite these therapeutic effects of MSCs‐exosomes, targeting intended tissues or cells while avoiding nonintended delivery still remains challenging.…”
Section: Discussionmentioning
confidence: 89%
“…However, when highly conserved biological pathways and processes are targeted, we believe the mouse to be a valid model for the prediction of clinical results of regenerative therapy. Beneficial effects of cardiac cell therapies have been mainly attributed to modulation of apoptosis [28, 29], inflammation and angiogenesis [30-33]. Intriguingly, these mechanisms are highly conserved biological pathways in mammals [34-36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSC-EXO significantly depressed lymphocyte proliferation, restrained the inflammatory response, and played a cardioprotective role. A decrease in the concentration of exosomes, results in the slower recovery of damaged hearts (Teng et al, 2015). Thus, further investigations are necessary to explain the transporter roles of MSC-EXO in wound healing and analyze the composition of exosomes to reveal their detailed mechanisms in chronic inflammation.…”
Section: How Mscs Function In Wound Inflammationmentioning
confidence: 99%